Dancing on Her Grave: The Murder of a Las Vegas Showgirl - Montan Diana; Sarassa, Carolina (New York Berkley Books, 2015)
Recounts the truth behind the brutal murder of Debbie Flores-Narvaez, a college graduate who went to Las Vegas to work as a showgirl and who was killed by a fellow dancer, Jason Griffith, who during the course of the trial is revealed to be a violent psychopath.
Keywords: Murder -- Nevada; Las Vegas; Case studies; Murder victims -- Nevada; Las Vegas; Case studies; Murder -- Investigation -- Nevada; Las Vegas; Case studies